Principles and practice of resistance training - Stone, Michael H. 1948-; Sands, Bill 1953-; Stone, Meg 1952- (Human Kinetics, 2007)
Principles and Practice of Resistance Training represents a true breakthrough in planning and monitoring strength training programs. This research-based book details how to systematically examine the physical, physiological, and biomechanical parameters associated with crafting resistance training programs to improve sport performance and strength and power in athletes. The authors bring together more than 100 collective years of teaching, conducting research, and coaching national- and international-level athletes to share their unique insights concerning adaptations to strength and conditioning. The text is written in a manner that challenges professionals while remaining accessible to advanced coaches. It begins by presenting readers with an understanding of basic science. This scientific foundation allows readers to formulate a sound training process that is more likely to produce the desired short- and long-term results. Next, the text examines how to test, monitor, and evaluate adaptations to various types of training programs. It emphasizes the significance of appropriately monitoring training programs to identify elements of the program to adjust so the goals of clients or athletes are more effectively and efficiently achieved. Finally, the authors discuss exercise selection and present a practical example so readers can learn to apply the information in the text to build their own training programs. Each chapter is written in a "stand-alone" manner so that readers can refer back to the material as needed. Principles and Practice of Resistance Training also explores key questions that currently have no clear, scientifically proven answers. For these issues, the authors offer reasoned, speculative explanations based on the best available information and data--including anecdotal evidence-- intended to stimulate additional observation and research that will eventually offer a clearer understanding and resolution of the issues involved. In sharing their personal experiences as coaches and research scientists, the authors are able to address issues that are not normally dealt with in academic programs. Principles and Practice of Resistance Training is far more than a general guide for strength training. It is an in-depth exploration of the science behind the training. Armed with the scientific understanding and the tools to put that information into practice, you will be able to develop training programs that help your athletes or clients excel.